The Impact of Shuttle Run Training on Sprint 100 Meters for Elementary School Students (9-10 Year Age Category) - Randy Pradana (INSPIREE: Indonesian Sport Innovation Review, 2022)
The purpose of the study.The background of this research is that the results of the sprint run conducted by Pahlawan Elementary School students, Bangkinang Kota are not optimal and are not appropriate in their implementation. Materials and methods. Research Methods This research uses a pre-experimental method with One Group, namely Pre-test and Post-test Design. The data collection technique was purposive sampling with inclusion and exclusion criteria. Data analysis in this study used the Wilcoxon test, Paired Sample T-test. Results. Research results based on the statistical output of "Test Statistics", it is known that Asymp.Sig (2-tailed) is worth 0.000. Because the value of 0.000 is smaller than <0.05. It can be concluded that "there is a significant difference between pre-test scores and post-test scores. test scores". Conclusions. Based on the results of data analysis, description, testing of research results and discussion, it can be concluded that there is a significant effect between shuttle run training and the results of the 100 meter sprint run for the Heroes Elementary School students, Bangkinang City, with the statistical output value "Test Statistics", known as Asymp. Sig (2-tailed) has a value of 0, 000. Because the value of 0, 000 is less than < 0, 05. So it can be concluded that "there is a significant difference between the pre test scores and post test".